Analisa Perbedaan Ratio Sproket Pada Sistem Transmisi Rantai - Paisal, Paisal; Gunawan, Yuspian; Samhuddin, Samhuddin (Teknik Mesin Universitas Halu Oleo, 2018)
The research aims to determine the difference ratio of chain transmission sprocket system, load and power that works on chain transmission. In this study the chain transmission system was designed using Autodesk inventor software which then analyzed the difference in sprocket ratio with calculations. Chain with number 40 ANSI standard as analysis data in this study. The results showed that the highest power of 6730,521 N and the load of 827,471 N were received in the C chain transmission system with a total of 34 front sprocket teeth and 17 rear sprocket teeth. Thehighest safety factor value of 21.833 in chain A transmission with the number of sprocket teeth 9 and 17.Keywords: Chain transmission design, ratio, load, safety factor